Aortopulmonary collaterals in single ventricle: incidence, associated factors and clinical significance. (25th July 2022) - Schmiel, Melvin; Kido, Takashi; Georgiev, Stanimir; Burri, Melchior; Heinisch, Paul Philipp; Vodiskar, Janez; Strbad, Martina; Ewert, Peter; Hager, Alfred; Hörer, Jürgen; Ono, Masamichi
Abstract : Aortopulmonary collaterals (APCs) represent an unpredictable source of pulmonary blood flow (PBF) in patients with univentricular heart and are observed in each stage of surgical reconstruction towards Fontan circulation, and also after the Fontan completion [1, 2]. Abstract: OBJECTIVES: Clinical significance of aortopulmonary collaterals (APCs) in patients with univentricular heart remains controversial. This study aimed to evaluate the incidence and associated factors for APCs and their influence during staged palliation. METHODS: In total, 430 patients who underwent staged palliation by bidirectional Glenn shunt and total cavopulmonary connection between 2003 and 2019 were examined. APCs were determined by angiogram. Incidence and interventions for APCs were analysed. RESULTS: The most frequent diagnosis was hypoplastic left heart syndrome in 146 (34%) patients. The median age at Glenn and Fontan was 4.9 months and 2.1 years, respectively. APCs were observed in 54 (13%) patients at Glenn and in 179 (42%) at Fontan. Closure of APCs was performed before Glenn in 12 (3%) patients, at Glenn in 13 (3%), after Glenn in 8 (2%), before Fontan in 44 (10%), at Fontan in 26 (6%) and after Fontan in 52 (12%). Hypoplastic left heart syndrome ( P < 0.01) was highly associated with the development of APCs before Glenn. Lower Nakata-Index and younger age at Glenn shunt were associated with the development of APCs at Fontan procedure. The presence of APCs or intervention for APCs before total cavopulmonary connection did not influence intensive care unit stay or mortality after total cavopulmonary connection. CONCLUSIONS: APCs were most frequently observed before Fontan procedure. Hypoplastic left heart syndrome was highly associated with the development of APCs before Glenn shunt. Lower Nakata-Index and younger age at Glenn shunt were associated with APCs before Fontan procedure.